ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT SEBAGAI INDIKATOR PERANAN BANK DALAM MENDORONG PEREKONOMIAN DI INDONESIA:Studi pada Bank Berdasarkan Struktur Kepemilikan Sesudah Krisis Global 2008 - wilman san, marino (2012)
Indonesia is the country that provides freedom of foreign ownership, which led to foreign domination in the banking sector. Global economic turmoil in 2008 have affected on the internal condition of the banking and macro economy in Indonesia. Under the conditions studied how the management policies of the bank with a different ownership structure of credit related decision as indicators in stimulating economic role of bank, on the terms of the internal condition indicated by ROA, and NPL BOPO while the external factors that the SBI interest rate margin with federal funds (ITL) and the Industrial Production Index (IPI). The analytical method used was Ordinary Least Square (OLS) with a significance level of 5%. The samples used in this research consisted of 22 commercial banks in Indonesia is divided into four structure holdings include the Government Bank, Domestic Dominance Bank, Foreign Domination Banks and Foreign Banks during the period July 2009 - June of 2011. Based on the obtained results of the research that ROA affect significantly positive to bank distribution credit on the Government Bank and Domestic Dominance Bank, while ROA had no significant effect to bank distribution credit of Foreign Domination Banks and Foreign Banks. BOPO affect significantly positive to bank distribution credit on the Government, Domestic Dominance Bank and Foreign Banks, while a significant negative effect on Foreign Domination Banks. NPL affect significantly negative to bank distribution credit on the Government Bank, Domestic Domination Bank and Foreign Domination Banks, while the NPL of Foreign Bank has no effect to bank distribution credit. ITL affect significantly positive to bank distribution credit on Domestic Dominance Bank, Foreign Domination Banks and Foreign Banks, while has no effect to bank distribution credit of the Government Bank. IPI affect significantly positive to bank distribution credit on the Government Bank, Domestic Dominance Bank, Foreign Domination Banks, while has no effect to bank distribution credit of the Foreign Bank. Based on the results of the research found that the Government Bank, Domestic Domination Bank, Foreign Domination Banks and Foreign Banks have less role in stimulating the economy by making credit distribution due the trend of changes in the main business of banking as an intermediary institution into activities that generate fee (fee-based income